2014
DOI: 10.36104/amc.2012.515
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis cutánea y peneana inducidas por warfarina

Abstract: Presentamos el caso de un hombre adulto mayor con múltiples episodios de trombosis venosa y arterial en diferentes localizaciones, quien desarrolló necrosis cutánea extensa y peneana pocos días después del uso de un antagonista de vitamina K (warfarina). Como parte del estudio de trombofilia se observó deficiencia de proteína C y S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was found that WSN developed within a time less than or equal to 15 days in 75% of patients receiving a median treatment time of 6.5 days, indicating that a proportion of people develop this complication late. Indeed, some authors described the WSN development after one month to 10 years of warfarin use and in whom treatment was reinitiated 4,21‐25 . Recent publications still consider a period of up to 3 years 26 ; however, we can state that it can be much longer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that WSN developed within a time less than or equal to 15 days in 75% of patients receiving a median treatment time of 6.5 days, indicating that a proportion of people develop this complication late. Indeed, some authors described the WSN development after one month to 10 years of warfarin use and in whom treatment was reinitiated 4,21‐25 . Recent publications still consider a period of up to 3 years 26 ; however, we can state that it can be much longer.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, some authors described the WSN development after one month to 10 years of warfarin use and in whom treatment was reinitiated. 4,[21][22][23][24][25] Recent publications still consider a period of up to 3 years 26 ; however, we can state that it can be much longer.…”
Section: Summary Of Evidence and Contrast With The Selected Literaturementioning
confidence: 95%